Preservation performance assessment in Greek libraries and archives; a practical tool to enable excellence - Gkinni, Zoitsa; Pavlogeorgatos, Gerasimos (Qualitative and Quantitative Methods in Libraries, 2017)
The quality of preservation in cultural institutions has not been adequately or systematically benchmarked across organisations. So far, different tools for different purposes have been developed by major institutions or states, to assist libraries and archives in assessing their preservation status and thus, to enable them, through prioritization to implement planned, preservation actions. The authors developed a diagnostic, easy to use yet comprehensive, self–assessment preservation performance tool to assist mainly medium size institutions, in measuring their preservation management quality level and thus plan a thoughtful preservation roadmap. The tool follows the results of a comprehensive, nationwide research that seeks to expand available knowledge on the Greek institutions’ preservation actions, policies and approaches to the preservation process. The tool will be available on the web and will be accompanied by an on-line guide. It will allow cultural institutions to make informed decisions about preservation actions, after their preservation maturity level has been defined and explained.